A Chequered Renaissance: The Evolution of Maori Society, 1984-2004 - Moon, Paul (Te Kaharoa, 2009)
This article traces aspects of the evolution of Maori society in the two decades following the Hui Taumata in 1984. Issues of language, political and self-determination, and Treaty settlements are explored for their contribution to this evolution.